Orchestrating Joyful Learning: Video Blogging to Build Self-Confidence in Language Learning - Putu Dian Danayanti Degeng; Nyoman Mega Sumamelati Degeng (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
This article describes the idea of how to orchestrate joyful language learning in digital era. For some language students, applying the theory into practice can be frustrating. One of the reasons is because they are lack of confidence. To be successful in language learning, it is important to have self-confidence. Teacher can build students’ self-confidence by giving a project that suit with their characteristics. Nowadays, students and technology cannot be separated. Students tend to use their gadget anytime and anywhere, including in class. Students’ dependency to technology provides various ways for the teacher to give practices to use language in a real world. Teacher can use the advantages which are brought by recent technology. One of the examples is video blogging. Video blogging can be used to build self-confidence in language learning. Furthermore, students can practice their speaking ability and other aspects in language within, and also learn to use technology in various ways. Orchestrating joyful language learning will give freedom for the students to learn as well as express their ideas. When the students are given the chance to do the projects that suit them, they will do it with passion and joy. The teacher’s role is to give enough space and let the students choose the best topic for the project. It is expected, by using video blogging to orchestrate joyful learning, the students will to learn will grow so they can use the language confidently.